EFEKTIVITAS PENERAPAN E-GOVERNMENT MELALUI SISTEM INFORMASI PELAYANAN PERIZINAN TERPADU (SIPPADU) DI KABUPATEN KUANTAN SINGINGI - Cici Malitha Wulandari; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The purpose of this study is to explain how the effectiveness of E-Government Implementation through Integrated Licensing Service Information System (SIPPADU) in Kuantan Singingi Regency. And explain what are the factors that hinder it. The theoretical concept used is the measurement of effectiveness by Siagian in (Wiraperdana, 2015). The research method used is a phenomenological approach to qualitative research, the selection of informants using purposive sampling technique. The technique of collecting data through observation, interviews and documentation. Research Results on the Effectiveness of E-Government Applications Through Integrated Licensing Services Information System (SIPPADU) in Kuantan Singingi District has not been effective due to several factors inhibiting network disruption, lack of training in employees, and lack of socialization to the community. It is better to achieve the success of the implementation of SIPPADU in Kuantan Singingi District, the government will increase what is the barrier to the implementation of SIPPADU.Keywords: Effectiveness, E-Government, Licensing Services